FORMAL MODEL OF PROJECT OR PROGRAM MENTAL SPACE - Bushuyev, S. D.; Verenych, O. V.; Bushuyev, D. A.; Jaroshenko, R. F. (Radio Electronics, Computer Science, Control, 2017)
Contex. A project or program mental space is one of the four mental spaces that are included in the wide mental space. A process of project or program implementation will be successful if the understanding of the purpose, values, approaches, project management methods are unambiguous for all participants of project or program creation and implementation. It allows reducing the time and effort to overcome misunderstandings between the project manager/project team, movable context, and stakeholders. A lack of unambiguous understanding often lead to troubles in project or program implementation, sometimes it can lead to failure in project or program implementation. The research and formalization of project or program mental space are timely. It allows project managers to see dependence between different mental space that are included in the wide mental space and to use methods and technics for influence on the project or program mental space for successful their implementation. The Objective of the work is to study the mental space of the project or program and its interaction with other mental space, and the development of formalized description of this space. In the paper, the methods of the mathematical set theory are used for presentation of project or program formalized description. The result is a combination of a content-related representation of the research objects, fixing their logical structure and investigation of the logical properties of the space. Conclusions. The study originality is creation and research of formalized model of project and program mental space. The practical approvement of the study was realized in the example of the project «Rural Land Titling and Cadaster System Development». It was the one of the biggest investment, an institutional and infrastructural project in Ukraine.